Case Report: Two Rare Cases of Complete Metabolic Response to Crizotinib in Patients With Rearranged ROS1 and ALK Metastatic Non-small Lung Cancer - Amrane, Karim; Campedel, Luca; Le Meur, Coline; Abgral, Ronan; Kharroubi, Dris; Cadranel, Jacques (Frontiers in Medicine, 2021)
Crizotinib is a tyrosine kinase inhibitor (TKI), indicated in first-line treatment of both rearranged ROS1 and ALK metastatic non-small lung cancer cancer (NSCLC). However, the reported common response after treatment is partial and few complete responses were reported in the PROFILE studies but with CT assessment. To date, only one case report of metabolic complete response FDG-PET/CT was published in a patient with ROS1 rearranged NSCLC. We highlighted the FDG-PET/CT useful approach for therapeutic assessment of TKI in metastatic mutated NSCLC reporting two complete metabolic responses in patients treated by crizotinib for a rearranged ROS1 and ALK metastatic NSCLC, respectively.